Don’t Forget To Ask Your T-Shaped Alumni! - Boateng, Adwoa (Qualitative and Quantitative Methods in Libraries, 2019)
What started out as a curiosity after having conversations with alumni about continued access to library databases became the author’s research focus of an exploratory study. Librarians conduct information literacy classes using databases as tools to help students develop research and analytical skills which employers expect. The expensive subscription costs of these library databases require routine scrutiny of their usage and content by librarians. The outcome of the exploratory study was very promising and indicated that alumni do want to be asked for feedback and suggestions. The author plans to use the study’s results as a guide for future studies as well as assessing the strengths, weaknesses, threats and opportunities (SWOT) of the author’s university science, health science and technology library database collection and library instruction.